Problems of Cross-Border Cooperation Between Poland and the Kaliningrad Oblast of the Russian Federation - Palmowski, Tadeusz (Quaestiones Geographicae, 2010)
Thanks to the opening of Europe to Kaliningrad and Kaliningrad to Europe, this region has been given an opportunity to gradually break the isolation which was the primary reason for its peripheral position. The enlargement of the Schengen Area complicated its relations and weakened cross-border cooperation with Poland. Further cross-border cooperation trends, though facing various barriers, may lead to improving the state of the natural environment in the Polish-Russian transborder region, joint planning of its development, growing mutual contacts, and making the populations living on both sides of the border more familiar with each other. Kaliningrad’s future also requires sustainable economic, ecological, social and political development. The working out of new principles of model cooperation between the EU and Russia may significantly stimulate the economy in the Polish-Russian cross-border areas. The mainstream options for opening Kaliningrad to regional cooperation can be an important step towards full integration of Baltic Europe.